2022
DOI: 10.1155/2022/8704016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PFKFB Preserves Intestinal Barrier Function in Sepsis by Inhibiting NLRP3/GSDMD

Abstract: Intestinal barrier dysfunction is associated with the occurrence and development of sepsis. Further, aerobic glycolysis plays an essential role in inflammation and cell death. This study is aimed at investigating the protective effect and mechanism of PFKFB3 inhibition on intestinal barrier dysfunction in sepsis mice. Sepsis mouse models were established by cecal ligation and puncture (CLP) in wild-type mice and Gsdmd-/- mice. The results showed that the expression of 6-phosphofructo-2-kinase/fructose-2,6-biph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Glycolysis is an important metabolic pathway controlled by many glycolytic enzymes, and previous reports have confirmed that gastric mucosal diseases utilise glycolysis to meet energy demands. [41][42][43] Based on a transcriptional sequencing assay of clinical PHT-induced injured gastric mucosal tissues combined with energy metabolism analysis of primary gastric mucosal epithelial cells from PHT model mice, we found that glycolysis was activated and regulated by the key rate-limiting enzyme LDHA in the gastric mucosa of PHT models under hypoxia. Elevated glycolysis and LDHA were also measured in GC cells and gastric mucosal tissues with cancerous lesions under hypoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is an important metabolic pathway controlled by many glycolytic enzymes, and previous reports have confirmed that gastric mucosal diseases utilise glycolysis to meet energy demands. [41][42][43] Based on a transcriptional sequencing assay of clinical PHT-induced injured gastric mucosal tissues combined with energy metabolism analysis of primary gastric mucosal epithelial cells from PHT model mice, we found that glycolysis was activated and regulated by the key rate-limiting enzyme LDHA in the gastric mucosa of PHT models under hypoxia. Elevated glycolysis and LDHA were also measured in GC cells and gastric mucosal tissues with cancerous lesions under hypoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that PFKFB3 may serve as a novel link between NLRP3 inflammasome-induced pyroptosis in trophoblasts [41]. Additionally, PFKFB3 has been implicated in the suppression of NLRP3-mediated pyroptosis [41,42]. Furthermore, Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…PFKFB3, a crucial glycolysis-regulating enzyme, is widely expressed in human tissues and has been shown to affect the pathogenic activity of diverse tissues [40,41]. Recent studies have shown that PFKFB3 expression is markedly enhanced in several animal models of disease, such as acute kidney injury, acute lung injury, and sepsis, and the underlying mechanisms have been investigated [42][43][44].…”
Section: Discussionmentioning
confidence: 99%